A porcine model of endothelial glycocalyx damage by enzymatic digestion: A pilot study - Astapenko, David; Ticha, Alena; Hyspler, Radomir; Tomasova, Adela; Navratil, Pavel; Maly, Ondrej; Parizkova, Renata Cerna; Cizkova, Dana; Huey, Shin Chua; Lehmann, Christian; Malbrain, Manu L N G; Cerny, Vladimir (Clinical hemorheology and microcirculation, 2021)
BACKGROUND: The endothelial glycocalyx (EG) plays a vital role in the physiology and pathophysiology of human microcirculation. Having relevant EG damage model would be important tool for testing new interventions aiming at EG protection and recovery. We describe the first in vivo EG damage model in pig. OBJECTIVE: To investigate the course of animal EG damage induced by specific enzymes. MATERIAL AND METHODS: Four anesthetized piglets received enzymes: 1g hyaluronidase and 25 IU heparanase I intravenously. Blood and urine samples were collected at baseline and 20/40/60/80/100/120 min for detecting markers of endothelial and EG function. Sublingual microcirculation and EG thickness were assessed by Side-stream Dark Field (SDF) imaging and Perfused Boundary Region (PBR) respectively. EG of the mesentery artery was visualized in fluorescent microscopy. RESULTS: Biochemical marker of EG damage syndecan-1 showed temporary increase with return to baseline and was reflected by PBR values. Albumin levels suggested brief period of capillary leakage (decrease in the serum, increase in the urine) with a trend to normalization. Urine glycosaminoglycans peaked at 120 minutes. Microcirculatory perfusion parameter showed significant alteration. Diffusion parameters were altered with no statistical significance. CONCLUSION: EG damage induced by specific enzymes was reflected by temporary changes of biochemical makers together with alteration of microcirculation and changes in fluorescent microscopy of EG layer. Our results support to further validate presented model of EG damage on a larger number of animals.
Keywords: trávení; Digestion; Pilot Projects; Swine; albuminuria; prasata; hyaluronidase; heparanase; glykokalyx; zvířata; Capillaries; Glycocalyx; endothelial glycocalyx; mikrocirkulace; Microcirculation; pilotní projekty; kapiláry; Animals